Shear fracture mechanism in micro-tension of an ultrafine-grained pure copper using synchrotron radiation X-ray tomography. (15th April 2017) - Li, Jianwei; Xu, Jie; Guo, Bin; Shan, Debin; Langdon, Terence G.
Abstract: In order to investigate the early fracture of ultrafine-grained (UFG) pure copper with a partially recrystallized microstructure and simple shear texture, the evolution of surface strain was measured using in situ micro-tension with digital image correlation. The spatial distribution of voids in tensile specimens was revealed after testing using synchrotron radiation X-ray tomography. The results show that the shear fracture behavior is associated with void evolution in UFG copper and this is strongly affected by the simple shear texture produced by equal-channel angular pressing (ECAP). The results have important implications for use in micro-forming. Graphical abstract: